Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Bursa Efek Indonesia - Alfiah, Devi Nur; Erlita, Alfiani Nila; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
The purpose of this research is to analyze and show empirically the effect of good corporate governance on company values. The hypothesis put forward is that good management functions as a fixed value as measured by Tobin's Q. This study uses secondary data from manufacturing companies listed on the Indonesia Stock Exchange. The procedure to be used in determining the research sample is a targeted sampling procedure. The analytical method used in this research is simple linear regression research. The results of the sample selection are 195 companies as research samples. The results of the classical acceptance test show that the data are normally distributed and there is no heteroscedasticity anomaly. The results of the hypothesis test show that good governance has a negative effect on firm value.